Lower Respiration in the Littoral Zone of a Subtropical Shallow Lake - They, Ng H.; Motta Marques, David d.; Souza, Rafael S. (Frontiers in Microbiology, 2013)
Macrophytes are important sources of DOC to littoral zones of lakes, but this DOC is believed to be mostly refractory to bacteria, leading to the hypothesis that bacterial metabolism is different in littoral and pelagic zones of a large subtropical shallow lake. We tested this hypothesis by three approaches: I) DIC accumulation in littoral and pelagic water; II) O2 consumption estimate for a cloud of points (n = 47) covering the entire lake; III) measurement of O2 consumption and CO2 accumulation in dark bottles, pCO2 in the water, lake-atmosphere fluxes of CO2 (fCO2) and a large set of limnological variables at 19 sampling points (littoral and pelagic zones) during seven extensive campaigns. For the first two approaches, DIC and O2 consumption were consistently lower in the littoral zone, and O2 consumption increased marginally with the distance to the nearest shore. For the third approach, we found in the littoral zone consistently lower DOC, total phosphorus (TP), and chlorophyll a, and a higher proportion of low-molecular-weight substances. Regression trees confirmed that high respiration (O2 consumption and CO2 production) was associated to lower concentration of low-molecular-weight substances, while pCO2 was associated to DOC and TP, confirming that CO2 supersaturation occurs in an attempt to balance phosphorus deficiency of macrophyte substrates. Littoral zone fCO2 showed a tendency to be a CO2 sink, whereas the pelagic zone showed a tendency to act as CO2 source to the atmosphere. The high proportion of low-molecular-weight, unreactive substances, together with lower DOC and TP may impose lower rates of respiration in littoral zones. This effect of perennial stands of macrophytes may therefore have important, but not yet quantified implications for the global carbon metabolism of these lakes, but other issues still need to be carefully addressed before rejecting the general belief that macrophytes are always beneficial to bacteria.